SARS-CoV-2 infectivity and antigenic evasion: spotlight on isolated Omicron sub-lineages - Barrera, Aldo; Martínez-Valdebenito, Constanza; Angulo, Jenniffer; Palma, Carlos; Hormazábal, Juan; Vial, Cecilia; Aguilera, Ximena; Castillo-Torres, Pablo; Pardo-Roa, Catalina; Balcells, María Elvira; Nervi, Bruno; Corre, Nicole Le; et al. (Frontiers in Medicine, 2024)
Since the SARS-CoV-2 outbreak in 2019, a diversity of viral genomic variants has emerged and spread globally due to increased transmissibility, pathogenicity, and immune evasion. By the first trimester of 2023 in Chile, as in most countries, BQ and XBB were the predominant circulating sub-lineages of Omicron. The molecular and antigenic characteristics of these variants have been mainly determined using non-authentic spike pseudoviruses, which is often described as a limitation. Additionally, few comparative studies using isolates from recent Omicron sub-lineages have been conducted. In this study, we isolated SARS-CoV-2 variants from clinical samples, including the ancestral B.1.1, Delta, Omicron BA.1, and sub-lineages of BA.2 and BA.5. We assessed their infectivity through cell culture infections and their antibody evasion using neutralization assays. We observed variations in viral plaque size, cell morphology, and cytotoxicity upon infection in Vero E6-TMPRSS2 cells for each variant compared to the ancestral B.1.1 virus. BA.2-derived sub-variants, such as XBB.1.5, showed attenuated viral replication, while BA.5-derived variants, such as BQ.1.1, exhibited replication rates similar to the ancestral SARS-CoV-2 virus. Similar trends were observed in intestinal Caco-2 cells, except for Delta. Antibody neutralization experiments using sera from individuals infected during the first COVID-19 wave (FWI) showed a consistent but moderate reduction in neutralization against Omicron sub-lineages. Interestingly, despite being less prevalent, BQ.1.1 showed a 6.1-fold greater escape from neutralization than XBB.1.5. Neutralization patterns were similar when tested against sera from individuals vaccinated with 3xBNT162b2 (PPP) or Coronavac-Coronavac-BNT162b2 (CCP) schedules. However, CCP sera showed 2.3-fold higher neutralization against XBB.1.5 than FWI and PPP sera. This study provides new insights into the differences between BA.2 and BA.5-derived variants, leading to their eventual outcompetition. Our analysis offers important evidence regarding the balance between infectivity and antigenic escape that drives the evolution of second-generation SARS-CoV-2 variants in the population.